Detection of circular excised DNA deletion elements in Tetrahymena thermophila during development. - Yao, M C (1994)
Extensive programmed DNA deletion occurs in ciliates during development. In this study we examine the excised forms of two previously characterized deletion elements, the R- and M-element, in Tetrahymena. Using divergently oriented primers in polymerase chain reactions we have detected the junctions formed by joining the two ends of these elements, providing evidence for the presence of circular excised forms. These circular forms were detected in developing macronuclear DNA from 12-24 h after mating began, but not in micronuclear or whole cell DNA of vegetative cells. They are present at very low abundance, detectable after PCR only through hybridization with specific probes. Sequence analysis shows that the circle junctions occur at or very near the known ends of the elements. There is sequence microheterogeneity in these junctions, which does not support a simple reciprocal exchange model for DNA deletion. A model involving staggered cuts and variable mismatch repair is proposed to explain these results. This model also explains the sequence microheterogeneity previously detected among the junction sequences retained in the macronuclear chromosome.